2021
DOI: 10.1016/j.jcmgh.2021.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Antibiotics Influence In Vivo and In Vitro Mouse Intestinal Epithelium Maturation and Functioning

Abstract: Background & Aims The use of antibiotics (ABs) is a common practice during the first months of life. ABs can perturb the intestinal microbiota, indirectly influencing the intestinal epithelial cells (IECs), but can also directly affect IECs independent of the microbiota. Previous studies have focused mostly on the impact of AB treatment during adulthood. However, the difference between the adult and neonatal intestine warrants careful investigation of AB effects in early life. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 102 publications
(176 reference statements)
1
32
2
Order By: Relevance
“…As of week 3, bodyweight was similar between AB-treated mice and control mice, which received PBS ( Figure 1 B). We previously showed that the intestinal permeability of P20 pups treated with the same early life AB mix was reduced compared to control pups [ 22 ]. To evaluate whether this difference in intestinal permeability persists into adulthood, we orally administered FITC-dextran to 8-week-old mice, that had been treated with AB in early life, and quantified its concentration in serum four hours later ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As of week 3, bodyweight was similar between AB-treated mice and control mice, which received PBS ( Figure 1 B). We previously showed that the intestinal permeability of P20 pups treated with the same early life AB mix was reduced compared to control pups [ 22 ]. To evaluate whether this difference in intestinal permeability persists into adulthood, we orally administered FITC-dextran to 8-week-old mice, that had been treated with AB in early life, and quantified its concentration in serum four hours later ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…The epithelial cells of the proximal and distal SI have different genetic profiles that support specific regional nutrient absorption and digestion functions, as well as different immune defense requirements [ 27 , 28 , 29 , 30 ]. We previously showed that these two SI regions are differently affected by early life AB treatment at P20 [ 22 ]; thus in the present study, we analyzed adult proximal and distal SI separately. Assessment of SI histology revealed no major morphological differences ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations